2020
DOI: 10.3390/cells9122569
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and Extracellular Vesicles as Emerging Theranostic Platforms in Cancer Research

Abstract: Exosomes are endosome-derived nanovesicles produced by healthy as well as diseased cells. Their proteic, lipidic and nucleic acid composition is related to the cell of origin, and by vehiculating bioactive molecules they are involved in cell-to-cell signaling, both in healthy and pathologic conditions. Being nano-sized, non-toxic, biocompatible, scarcely immunogenic, and possessing targeting ability and organotropism, exosomes have been proposed as nanocarriers for their potential application in diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 112 publications
0
54
0
Order By: Relevance
“…Similarly, Naseri et al have reported the bone marrow-derived MSC-Exo as proper nanocarriers for therapies based on RNA applications [ 70 ]. Different studies using confocal laser scanning microscopy and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) revealed the fact of joining and absorption of exosomes derived from MSCs with the lipid bilayer membrane of the breast cancer cells [ 70 , 71 ]. Furthermore, an in vitro study on exosomes derived from MSCs including miR-100, as a tumor-suppressive miRNA, on MDA-MB-231 and MCF-7 cells indicated a decrease in the expression level of mTOR and HIF-1 α and suppressed VEGF expression involved in angiogenesis control [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Naseri et al have reported the bone marrow-derived MSC-Exo as proper nanocarriers for therapies based on RNA applications [ 70 ]. Different studies using confocal laser scanning microscopy and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) revealed the fact of joining and absorption of exosomes derived from MSCs with the lipid bilayer membrane of the breast cancer cells [ 70 , 71 ]. Furthermore, an in vitro study on exosomes derived from MSCs including miR-100, as a tumor-suppressive miRNA, on MDA-MB-231 and MCF-7 cells indicated a decrease in the expression level of mTOR and HIF-1 α and suppressed VEGF expression involved in angiogenesis control [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from their fundamental roles in the organism, EVs can have valuable functions as either diagnostic or therapeutic agents, or the combination of both, known as theranostics tools. EVs reflect the physiological state of the cell they originate from, and they are readily available in biofluids, and as such, they can be used in novel diagnostic platforms [5,34]. This is especially important for the diagnosis of diseases in organs in which tissue biopsy should be avoided whenever possible, such as brain or kidneys.…”
Section: Main Proposed Functions Of Extracellular Vesiclesmentioning
confidence: 99%
“…Exosomes are the smallest form of extracellular vesicles that range from 50 to 100 nm [3]. Besides these three main subtypes, other extracellular vesicles include membrane particles, exosome-like vesicles, neutrophil originating extracellular vesicles (ectosome) [4], prostate originating extracellular vesicles (prostasomes) [5], migrasomes [6], oncosomes, large oncosomes [7], tolerosomes (from intestinal epithelial cells) [8], gesicles [9] and prominosomes (luminal fluid of embryonic neural tube) [10]. Exosomes were discovered in 1983 when it was found that reticulocyte releases 50 nm small vesicles that carry transferrin receptors into the extracellular space [11,12].…”
Section: Introductionmentioning
confidence: 99%